Guest Editors’ Notes: Communication, Media, And Its Impact in Times of Crisis - Suria Hani A. Rahman; Fauziah Hassan; Wan Mohd Fazrul Azdi Wan Razali (USIM Press, 2024)
Vol. 33 No. S5 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences